Women’s Role in Religious and Educational Activities in the Prophetic Era - Muhammad Azam; Dr. Hafiz Muhammad Afzal (Journal of Religion and Society, 2025)
This article explores the significant religious, educational, and social roles Muslim women played during the Prophetic era, highlighting their vital contributions to Seerah al-Nabi. Far from being passive observers, women were actively involved in learning, teaching, narrating Hadith, and supporting the spread of Islam through both scholarship and sacrifice. Key figures such as Hazrat Khadijah (RA), Hazrat Aisha (RA), and Hazrat Umm Salama (RA) were foundational in shaping early Islamic knowledge and character. Their homes became centers of learning, and their narrations and legal opinions became references for generations. Women like Hazrat Fatimah (RA), Hazrat Safiyyah (RA), and Hazrat Umm Ammarah (RA) combined religious devotion with social activism and even military engagement. Female companions contributed to educational pursuits, medicine, Qur’anic memorization, and calligraphy showcasing Islam's encouragement of women’s intellectual growth. This article emphasizes that the Prophet Muhammad (ﷺ) not only endorsed women’s education but also ensured they had separate gatherings for learning. Their sacrifices, such as that of Sumayyah (RA), the first female martyr, and their leadership in society continue to guide modern Muslim women in faith and service. Keywords: Women, Prophetic Era, Seerah al-Nabi, Sahabiyat, Islamic Education, Religious Contribution